2015
DOI: 10.4038/tare.v16i2.5273
|View full text |Cite
|
Sign up to set email alerts
|

Quality of minimally processed modified atmosphere sorted bell pepper , as affected by pre treatments

Abstract: Minimally processed bell pepper strips stored at 8-10 0 C for seven days were evaluated for variation in color, in package gases, firmness, physicochemical sensory and microbiological quality. Bell pepper strips were treated with sodium chloride, calcium chloride, sodium chloride+calcium chloride or distilled water (control) and packed in polystyrene packages before storage. Pretreatments did not drastically affect the physicochemical properties (titratable acidity (TA), total soluble solids (TSS) and pH) when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
1
0
0
Order By: Relevance
“…During the storage period, it was observed that the samples which had more deterioration showed greater values of total colour difference (Δ E ) (Figure a–e). The increase in Δ E value was observed in all the samples and was in accordance with studies done by Ediriweera et al, () and Ranjitha, Rao, Shivshankara, and Roy () which stated that ΔE increased during storage of capsicum shreds. All the experiments, showed no immediate effects of ozone on colour after the treatments.…”
Section: Resultssupporting
confidence: 91%
“…During the storage period, it was observed that the samples which had more deterioration showed greater values of total colour difference (Δ E ) (Figure a–e). The increase in Δ E value was observed in all the samples and was in accordance with studies done by Ediriweera et al, () and Ranjitha, Rao, Shivshankara, and Roy () which stated that ΔE increased during storage of capsicum shreds. All the experiments, showed no immediate effects of ozone on colour after the treatments.…”
Section: Resultssupporting
confidence: 91%